Therapeutic landscapes, outdoor programs for veterans, and public lands. (January 2021) - Havlick, David G.; Cerveny, Lee K.; Derrien, Monika M.
Abstract: In recent decades, scholars have developed ideas about therapeutic landscapes that explore how social processes, symbolism, and physical features generate diverse meanings. We examine here how therapeutic landscapes are produced and utilized for outdoor programs for military veterans, particularly veterans experiencing post-traumatic stress. Outdoor programs for veterans (OPVs) provide restorative opportunities through nature immersion and outdoor recreation. OPVs involve diverse social settings, activity types, durations, geographic and land management contexts, and degrees of therapeutic intervention. In many combinations they can generate therapeutic landscapes conducive to some degree of recovery. Our analysis relies on qualitative data gathered through semi-structured interviews with OPV providers and participants, mental health specialists, and public land officials. Arguing against a reductionistic approach, we suggest that the diversity of OPVs and disparate character of activities, locations, and dosages may contribute in important ways to the efficacy of these programs. Ironically, the very qualities that present challenges for measuring and evaluating the benefits of OPVs may prove to be advantageous with respect to therapeutic outcomes. We highlight how public lands present a distinctive set of attributes that make them particularly well-suited to provide therapeutic opportunities, and that agency policies can shape the development of therapeutic landscapes. Highlights: Outdoor programs for veterans (OPVs) vary in activity, location, and duration. The diversity of OPVs may contribute to their overall efficacy. Therapeutic landscapes produced by OPVs depend on social and environmental features. Public lands are well-suited to offer therapeutic opportunities. Land managers shape the scope, quality, and availability of therapeutic landscapes.